HUBUNGAN KESEJAHTERAAN PEGAWAI DENGAN SEMANGAT KERJA DI UPTD TAMAN BUDAYA JAMBI - Laila Farhat; Marnas, Marnas; Abdul Wahab Daeng (Bajang Institute, 2024)
This research aims to determine the influence of employee welfare on employee morale at UPTD Taman Budaya Jambi. This research used a questionnaire with 36 respondents who were UPTD Taman Budaya Jambi employees. From the results of data processing using SPSS, the regression equation model Y = 9.129 + 0.719X was obtained. From the results of data processing, an R Square value (coefficient of determination) was also obtained of 0.816, which means that the influence of the Employee Welfare variable (X) on Employee Work Morale (Y) was 81.6%. This shows that by using the regression model, the independent variable, namely the Employee Welfare variable (X), has an influence on Employee Work Morale (Y) of 81.6% while the remaining 18.4% is explained by other factors or variables not included in the analysis. this regression. From the results of this research, the conclusion is drawn that